Teaching English in Multilingual Contexts EFL Teachers’ Perceptions and Experiences - Bhattarai, Prakash (Journal of NELTA, 2025)
Teaching the English language, promoting multilingualism is a challenging job for English as foreign language (EFL) teachers. They need to teach the English language on one hand and promote multilingualism on the other. In this scenario, this article explores how EFL teachers perceive teaching the English language in multilingual contexts and how they promote and preserve multilingualism in their classrooms. For this purpose, data were collected through in-depth interviews with three purposively selected secondary-level EFL teachers teaching in three different districts in Nepal. After analyzing the data using the thematic analysis method, it was found that EFL teachers focus on promoting the English language since teaching and learning English opens the doors for a host of opportunities, they promote multilingualism giving space to students’ mother tongues in English classes, and they address the linguistic diversity found in their classroom and promote multilingualism in the course of teaching English with the help of trans language pedagogy.